Gas gushing damping mechanism and its engineering application of bottom hole combined drilling tool - Yonglong WANG; Yuxiang PEI; Yuning SUN; Zaijiang YU; Lipei DING; Yue WU; Jiakuan GUO; Kang DU (Meitan xuebao, 2023)
In order to solve the technical problem of gas blowhole over-limit in gas drainage holes, a method of weakening the gas gushing in the borehole was proposed. The structural model of a hole-bottom combined damping drilling tool was constructed. By establishing airflow resistance mechanics equation and numerical simulation of damping effect of the hole-bottom combined damping drilling tool, the analysis of gas gushing mechanism of the hole-bottom combined damping drilling tool and the industrial test of on-site hole drilling were carried out. The hole-bottom combined damping drilling tool was developed, including exposing drill bit, melting coating damping drill pipe and reaming drill bit. The research results show that ① the drilling tool reduces the exposed area at the bottom of the hole and increases the resistance of the high-pressure gas flow at the spray hole source, which are the keys to the weakened gas gushing pressure technology. By rationally designing the “depressurization gap” β, changing the relative roughness of the drilling tool, increasing the resistance coefficient along the path, and increasing the wind resistance, the pressure of the ejected gas can be reduced to less than 25% of the initial value. ② The numerical calculations show that the hole-bottom combined damping drilling tool can greatly weaken the airflow pressure of the nozzle orifice, and reduce the risk of high-pressure air current jetting out at high speed at the orifice. The study reveals that the “depressurization gap” formed by the drill bit and the damping drill pipe plays a decisive role in the damping effect. ③ The hole-bottom combined damping drilling tool was used for construction on site. The opening of the drilling tool water supply valve was fully opened, and the drilling speed was slightly reduced. At the same time, two obvious gas fluctuations were detected at the hole of the drilling hole, and gas was detected at the orifice. In the area, there was no gas over-limit in the nozzle hole, indicating that the combined damping drilling tool at the bottom of the hole has a significant weakening effect on the gas gushing pressure in the hole. The blowout pressure of the orifice blowout preventer is reduced.